Adherence of older women with strength training and aerobic exercise - Picorelli AMA (Dove Medical Press, 2014)
Alexandra Miranda Assumpção Picorelli, Daniele Sirineu Pereira, Diogo Carvalho Felício, Daniela Maria Dos Anjos, Danielle Aparecida Gomes Pereira, Rosângela Corrêa Dias, Marcella Guimarães Assis, Leani Souza Máximo Pereira Graduate Program in Rehabilitation Sciences, Department of Physical Therapy, Universidade Federal de Minas Gerais, Belo Horizonte, Minas Gerais, Brazil Background: Participation of older people in a program of regular exercise is an effective strategy to minimize the physical decline associated with age. The purpose of this study was to assess adherence rates in older women enrolled in two different exercise programs (one aerobic exercise and one strength training) and identify any associated clinical or functional factors. Methods: This was an exploratory observational study in a sample of 231 elderly women of mean age 70.5 years. We used a structured questionnaire with standardized tests to evaluate the relevant clinical and functional measures. A specific adherence questionnaire was developed by the researchers to determine motivators and barriers to exercise adherence. Results: The adherence rate was 49.70% in the aerobic exercise group and 56.20% in the strength training group. Multiple logistic regression models for motivation were significant (P=0.003) for the muscle strengthening group (R2=0.310) and also significant (P=0.008) for the aerobic exercise group (R2=0.154). A third regression model for barriers to exercise was significant (P=0.003) only for the muscle strengthening group (R2=0.236). The present study shows no direct relationship between worsening health status and poor adherence. Conclusion: Factors related to adherence with exercise in the elderly are multifactorial. Keywords: older women, adherence, therapeutic exercises